Interpretation of Endocervical Cells With Gastric-Type Mucin on Pap Smears: A Proposal for a Cytologic Category "Atypical Endocervical Cells With Gastric-Type Mucin". Issue 3 (5th July 2018) - Omori, Makiko; Kondo, Tetsuo; Nakazawa, Kumiko; Tagaya, Hikaru; Ohgi, Maki; Fukasawa, Hiroko; Nakazawa, Tadao; Hashi, Akihiko; Hirata, Shuji
Abstract: Objectives: Early detection of endocervical adenocarcinoma is especially important for cancers that are human papillomavirus (HPV) negative. We investigated the clinicopathologic significance of yellow gastric-type mucin observed on Papanicolaou smears. Methods: We described "atypical endocervical cells with gastric-type mucin" (AEC-GAM) when yellow mucin was observed in endocervical cells. We retrieved AEC-GAM samples from 58, 752 cervical smears performed at Yamanashi University Hospital during our study period and reviewed clinical, cytologic, and pathologic features. Results: We detected AEC-GAM in 172 (0.29 %) smears from 65 patients, and 41 of these 65 patients were histologically diagnosed with lobular endocervical glandular hyperplasia (LEGH) (43%) or pyloric gland metaplasia (20%). The prevalence of adenocarcinoma was 25% (7/28) in LEGH cases and 11% (7/65) in AEC-GAM smears. Conclusions: Yellow mucin is a diagnostic clue for endocervical glandular lesions with gastric differentiation. We recommend describing AEC-GAM on cytologic reports to improve cytologic screening for HPV-negative cervical cancers.